Lezen : teksten over het archief - Bos-Rops, Yvonne; Janssens, Gustaaf; Jeurgens, Charles; Ketelaar, Eric ('s-Gravenhage: Stichting Archiefpublicaties, 2009)
"redactie Yvonne Bos-Rops, Gustaaf Janssens, Charles Jeurgens, Eric Ketelaar"